2001
DOI: 10.1017/s0074180900221451
|View full text |Cite
|
Sign up to set email alerts
|

M 31's Molecular Arms at All Scales to Below 10 pc

Abstract: Abstract. I present a unique data set for the study of molecular gas in galaxies: a complete, high-resolution survey of the CO in M 31 and additional local studies. The fully sampled survey has an angular resolution of 23" FWHM and the interferometric data attain the pc-scale with subarcsecond resolution. For the first time it is now possible to study large and small scales in conjunction. Thus we are able to derive the global structure and study the links down to the individual cloud complexes and star format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 5 publications
4
26
0
Order By: Relevance
“…In regions with CO emission, the excess dust emission with respect to this ratio indicates the mass of H 2 . This technique has been succesfully applied to M 51, NGC 891, NGC 4565 and to some nearby irregular galaxies such as the Magellanic Clouds (Guélin et al 1995;Guélin et al 1993;Neininger et al 1996;Israel 1997).…”
Section: An Alternative Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In regions with CO emission, the excess dust emission with respect to this ratio indicates the mass of H 2 . This technique has been succesfully applied to M 51, NGC 891, NGC 4565 and to some nearby irregular galaxies such as the Magellanic Clouds (Guélin et al 1995;Guélin et al 1993;Neininger et al 1996;Israel 1997).…”
Section: An Alternative Methodsmentioning
confidence: 99%
“…The technique applied by Guélin and collaborators to a few nearby galaxies (Guélin et al 1993(Guélin et al , 1995Neininger et al 1996; see also Israel 1997) seems very promising. It consists of determining the amount of dust from millimetric/submillimetric observations and correlating it with CO and HI.…”
Section: Introductionmentioning
confidence: 99%
“…The strong submillimeter emission found in all the observed galaxies could not be accounted for by dust emitting at a uniform temperature, and the far-infrared (FIR) spectra were interpreted in terms of two dust components of about 16 and 53 K. This interpretation suggested that the peak of the FIR emission should be at wavelengths between 100 and 200 km. Subsequent submillimeter observations done with the 30 m IRAM (Pico Veleta) telescope also suggested the presence of a cold dust component in individual nearby galaxies : NGC 891 et al 1993), NGC 3627 (Guelin (Sievers et al 1994), NGC 4631 (Braine et al 1995), M51 et al 1995), NGC 4565 (Neininger et al 1996), NGC (Guelin 3079 , and NGC 5907 . The enhanced sensitivity and overall efficiency improvement of the Submillimeter Common-User Bolometric Array on the James Clerk Maxwell Telescope extended our knowledge of the quantity of cold dust by probing both more "" quiescent ÏÏ galaxies and also by mapping its distribution with higher resolution (Alton et al 1998a(Alton et al , 2001Israel, Van Der Werf, & Tilanus 1999 ;Bianchi et al 2000b).…”
Section: Introductionmentioning
confidence: 94%
“…To these, we can add 71 galaxies observed along the major axis during the FCRAO CO survey of nearby galaxies by Young et al (1995). Another object, NGC 4565, has also been partly mapped with the IRAM 30 m (Neininger et al 1996) and with the 45 m Nobeyama (Sofue & Nakai 1994) radiotelescopes. Because of the complete coverage of the stellar disc, in particular for the single-dish observations done at the Nobeyama, IRAM, and FCRAO radio telescopes, we consider that all these data are of much higher quality than other singlebeam observations that require aperture corrections.…”
Section: Total Co Fluxesmentioning
confidence: 99%
“…We thus end up with 37 HRS galaxies with integrated data, 17 from Kuno et al (2007), 0 from Helfer et al (2003) 4 , 6 from Chung et al (2009a), and 13 from Young et al (1995). To these we can add a galaxy, NGC 4565 (HRS 213), partly mapped by Neininger et al (1996) with the IRAM radiotelescope and by Sofue & Nakai (1994) with the Nobeyama radiotelescope. By correcting their own independent sets of data to extend the measure of the CO flux to the whole galaxy, they end up with a total flux of SCO = 1672.2 Jy km s −1 and SCO = 1643 Jy km s −1 , respectively.…”
Section: Data Ismentioning
confidence: 99%